2005
DOI: 10.1016/j.cell.2005.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 4D Deficiency in the Ryanodine-Receptor Complex Promotes Heart Failure and Arrhythmias

Abstract: Phosphodiesterases (PDEs) regulate the local concentration of 3',5' cyclic adenosine monophosphate (cAMP) within cells. cAMP activates the cAMP-dependent protein kinase (PKA). In patients, PDE inhibitors have been linked to heart failure and cardiac arrhythmias, although the mechanisms are not understood. We show that PDE4D gene inactivation in mice results in a progressive cardiomyopathy, accelerated heart failure after myocardial infarction, and cardiac arrhythmias. The phosphodiesterase 4D3 (PDE4D3) was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
460
0
16

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 460 publications
(512 citation statements)
references
References 39 publications
25
460
0
16
Order By: Relevance
“…While the lack of selective inhibitors of PDE4 isoforms has made it particularly difficult in understanding the roles of PDE4 subfamilies, gene mutation and RNA interference (RNAi) have been shown to be feasible approaches to identifying functions of PDE4 subfamilies and even their variants (Lehnart et al, 2005;Lynch et al, 2005;Terrin et al, 2006;Zhang et al, 2002). Using genetic deletion mutants of specific PDE4 subtypes (Hansen et al, 2000;Jin et al, 2005b), it has been shown that PDE4D is important for antidepressant activity (Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…While the lack of selective inhibitors of PDE4 isoforms has made it particularly difficult in understanding the roles of PDE4 subfamilies, gene mutation and RNA interference (RNAi) have been shown to be feasible approaches to identifying functions of PDE4 subfamilies and even their variants (Lehnart et al, 2005;Lynch et al, 2005;Terrin et al, 2006;Zhang et al, 2002). Using genetic deletion mutants of specific PDE4 subtypes (Hansen et al, 2000;Jin et al, 2005b), it has been shown that PDE4D is important for antidepressant activity (Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Comme pour la PDE3, l'étude de souris invalidées pour les gènes PDE4A, PDE4B et PDE4D a permis de mieux comprendre le rôle des trois différents sous-types de PDE4 dans le CEC. Ces travaux ont permis de montrer qu'une isoforme issue du gène PDE4B régule préféren-tiellement le courant calcique de type L [29], tandis que les isoformes issues du gène PDE4D régulent préférentiellement les flux calciques du RS [30,31] (Figure 2). En effet, il a d'abord été montré que, dans régulation de l'influx calcique transitant par les canaux LTCC, tandis que la PDE4D régule la recapture de calcium par le RS et, peut être aussi, sa libéra-tion par les RyR2 (Figure 2).…”
Section: Régulation Du Cec Par Les Pde4unclassified
“…Ceci pourrait être lié à la contribution importante de la PDE4 dans cette espèce. De fait, in vivo, les souris PDE4B -/-et PDE4D -/-présentent une susceptibilité les souris PDE4D -/-, la perte d'un variant particulier (PDE4D3) de ce gène normalement associé au RyR2, provoque l'hyperphosphorylation de ces récepteurs par la PKA, ce qui augmente leur activité [31]. L'éli-mination du gène PDE4D entraîne aussi la phosphorylation accrue du PLB, et une isoforme longue du gène PDE4D est co-immunoprécipitée avec la pompe SERCA2 [30].…”
Section: Implications Physiopathologiquesunclassified
See 2 more Smart Citations